Start up of biological sequencing batch reactor (SBR) and short‐term biomass acclimation for polyhydroxyalkanoates production. Issue 2 (10th May 2012) - Valentino, Francesco; Brusca, Angelo Antonio; Beccari, Mario; Nuzzo, Andrea; Zanaroli, Giulio; Majone, Mauro
Abstract: BACKGROUND: The adaptation/selection of mixed microbial cultures under feast/famine conditions is an essential step for polyhydroxyalkanoates (PHA) production. This study investigated the short‐term adaptation of a mixed microbial culture (activated sludge) during the start up of a sequencing batch reactor (SBR). RESULTS: Four different SBR runs were performed starting from different inocula and operated at the same organic load rate (8.5 gCOD L −1 d −1 ) and hydraulic retention time (1 day). At 3–7 days from SBR start up, the selected biomass was able to store PHA at comparable rate and yield with those obtained after long‐term acclimation. Independently from the time passed, a short feast phase was the key parameter to obtain PHA storage at high rate and yield in the following accumulation stage (244 mgCOD g −1 CODnonPolym h −1 for specific storage rate and 48% COD COD −1 as PHA content in the biomass). The DGGE profiles showed that the good storage performance and the structure of the microbial community were not fully correlated. CONCLUSIONS: The results suggest a new strategy for operating the PHA accumulation stage directly in the SBR, after very short biomass adaptation, instead of using two separate reactors for biomass enrichment and PHA accumulation, respectively. © 2012 Society of Chemical Industry